The tumor suppressor LKB1 regulates starvation-induced autophagy under systemic metabolic stress - Laurie A. Mans (Nature Portfolio, 2017)
Abstract Autophagy is an evolutionarily conserved process that degrades cellular components to restore energy homeostasis under limited nutrient conditions. How this starvation-induced autophagy is regulated at the whole-body level is not fully understood. Here, we show that the tumor suppressor Lkb1, which activates the key energy sensor AMPK, also regulates starvation-induced autophagy at the organismal level. Lkb1-deficient zebrafish larvae fail to activate autophagy in response to nutrient restriction upon yolk termination, shown by reduced levels of the autophagy-activating proteins Atg5, Lc3-II and Becn1, and aberrant accumulation of the cargo receptor and autophagy substrate p62. We demonstrate that the autophagy defect in lkb1 mutants can be partially rescued by inhibiting mTOR signaling but not by inhibiting the PI3K pathway. Interestingly, mTOR-independent activation of autophagy restores degradation of the aberrantly accumulated p62 in lkb1 mutants and prolongs their survival. Our data uncover a novel critical role for Lkb1 in regulating starvation-induced autophagy at the organismal level, providing mechanistic insight into metabolic adaptation during development.